Pengaruh Team Building terhadap Efektivitas Work Teams: Studi pada Mahasiswa Universitas Muhammadiyah Bandung - Tini Kartini; Yesi Amelia; Anggi Mahmudin; Sofa Parihah Nurasiah (INDO PUBLISHING, 2026)
Team effectiveness is widely regarded as a key determinant of organizational success, including in student organizations whose programs are largely carried out through collective teamwork. This study aims to examine and analyze the effect of team building on the effectiveness of work teams among students at Universitas Muhammadiyah Bandung who are active in student organizations. The study employs a quantitative approach with a descriptive-verificative design. Primary data were collected through a Likert-scale questionnaire distributed to students who had participated in team-building activities and were directly involved in organizational teamwork. The collected data were tested for validity and reliability, followed by classical assumption tests, before being analyzed using simple linear regression to determine the direction and strength of the relationship between the two variables. The results show that team building falls into the good category (TCR 81.2%), as does work team effectiveness (TCR 80.8%). Team building was found to have a positive and significant effect on work team effectiveness (t = 9.823; sig. = 0.000), accounting for 77.5% of its variance (R Square = 0.775). These findings confirm that better implementation of team building corresponds to higher work team effectiveness, and are expected to provide practical input for student organization leaders in designing more focused team-development programs.